Effect of Nanosilica and Bentonite as Mycotoxins Adsorbent Agent in Broiler Chickens’ Diet on Growth Performance and Hepatic Histopathology - Abdallah A. Ghazalah; Mamduh O. Abd-Elsamee; Kout Elkloub M. E. Moustafa; Mohamed Abdelrazik Khattab; Abd-Elrahim A. A. Rehan (Animals, 2021)
Mycotoxins are toxic secondary metabolites produced by different strains of fungi, such as aspergillus, fusarium, and penicillium that can contaminate feed ingredients or the entire feed of poultry and animals. Mycotoxins can cause many serious complications to both humans and animals due to carcinogenic, mutagenic, and immunosuppressive disorders. Therefore, the present experiment aims to investigate the effect of broiler chickens’ diets supplemented with different levels of nanosilica (NS) as an adsorbent agent of mycotoxins on their growth performance and hepatic histopathology. Detectable levels of toxins were present in the feed before feeding, and all levels of mycotoxins were above the normal limit. A total of 180 one-day-old male Arbor Acres broiler chickens were allocated randomly to six treatment groups with three replicates per group, including ten chickens per replicate. The experiment lasted for five weeks, and dietary treatments included control diet and diets with four levels of nanosilica as 0.05%, 0.10%, 0.15%, and 0.20% as well as 0.50% bentonite (fixfin® Dry) diet. Bodyweight, body weight gain, average daily feed intake, and feed conversion ratio were measured weekly. At the end of the fifth week, six chickens per treatment were sacrificed to investigate the effects of NS and bentonite on carcass characteristics and hepatic histopathology. The results showed that providing broiler chickens’ diets with an adsorbent agent, such as NS or bentonite, can reduce the side effects of mycotoxins and enhance their growth performance. The best record was achieved with NS at 0.20%, compared with the control group and other dietary treatment groups. Accordingly, 0.20% of NS could be used in broiler chickens’ diets to minimize the harmful effects of mycotoxins.